Lassa fever: another infectious menace (2009)
Nigeria is presently suffering from another Lassa fever epidemic. This was confirmed in the statement of the Minister of Health of the Federation in which he said, “There has been an upsurge in the reported cases of Lassa fever since the beginning of this year, especially in the Federal Capital Territory and its environs. Within two weeks, 12 cases with five deaths due to the disease were recorded. 25 contacts are confirmed by laboratory investigations to have been infected, including 4 health staff working in the National Hospital, Abuja.”1 Lassa fever is an acute viral haemorrhagic fever first described in 1969 in the town of Lassa in Borno state, Nigeria.2 It is endemic in West African countries, and causes 300,000 cases annually with 5000 deaths.3 Lassa fever epidemics occur in Nigeria, Liberia, Sierra Leone, Guinea and the Central African Republic.4 Lassa virus, the agent of the disease is a member of the Arenaviridae family. The virus is pleomorphic with single-stranded and bisegmented RNA genome.3 Its primary host is Natal Multimammate Mouse (Mastomys natalensis). Transmission to man occurs via exposure to the rat excrement through respiratory or gastrointestinal tracts5, exposure of broken skin or mucus membrane to infected material, direct contact, sexually and transplacentally. The prevalence of antibodies to the virus is 8-22%9 in Sierra Leone, 4-55% in Guinea,12 and 21% in Nigeria.13 The disease is mild or asymptomatic in 80% of infected people, but 20% have a severe multisystemic disease. Clinical features are difficult to differentiate from that of other viral haemorrhagic fevers and common febrile illness such as Malaria, Typhoid fever and so on. Definitive diagnosis is by viral isolation, Antigen and Antibody detection and Reverse Transcriptase PCR. Treatment is with Ribavirin, an antiviral agent. No vaccine is currently available. Prevention is by keeping rats away from homes.